2014
DOI: 10.1111/dsu.12438
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prevalence of Surgical Site Infection with Use of Sterile Versus Nonsterile Gloves for Resection and Reconstruction During Mohs Surgery

Abstract: The prevalence of infection with SG and NSG was almost identical. The cost to use SG was 3.5 times as great as for NSG. The use of NSG for MMS and reconstruction is safe and cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 13 publications
(19 reference statements)
1
39
0
12
Order By: Relevance
“…Although studies have demonstrated a statistically significant difference in bacterial load favoring use of SG, the clinical significance of this finding is uncertain. 47 A recent Cochrane review evaluating the use of disposable face masks for preventing SSI in clean surgery identified 3 studies, which demonstrated no statistically significant differences between masked versus unmasked SSI rates; however, because of the small number of trials and limitations of the included studies, it is currently unclear if the use of surgical face masks alters SSI rates. 46 Furthermore, a more recent study demonstrated that the prevalence of SSI in SG versus NSG was almost identical, and the cost of SG is 3.5 times greater.…”
Section: Surgical Attirementioning
confidence: 99%
“…Although studies have demonstrated a statistically significant difference in bacterial load favoring use of SG, the clinical significance of this finding is uncertain. 47 A recent Cochrane review evaluating the use of disposable face masks for preventing SSI in clean surgery identified 3 studies, which demonstrated no statistically significant differences between masked versus unmasked SSI rates; however, because of the small number of trials and limitations of the included studies, it is currently unclear if the use of surgical face masks alters SSI rates. 46 Furthermore, a more recent study demonstrated that the prevalence of SSI in SG versus NSG was almost identical, and the cost of SG is 3.5 times greater.…”
Section: Surgical Attirementioning
confidence: 99%
“…Rhinehart and colleagues undertook the first study in 2006 to investigate this issue. Mehta and colleagues 67 performed a similar study in 2011 to 2012 but included a larger collection of material, reviewing 942 patients repaired with sterile gloves and 941 patients with nonsterile gloves. 64 A prospective trial in 2007 by Rogues and colleagues, examining 3,491 dermatosurgical wounds in patients undergoing reconstructive procedures (flaps or grafts), found a significantly higher rate of SSIs when nonsterile gloves were used compared with sterile gloves (14.7% vs 3.4%).…”
Section: Surgical Glovesmentioning
confidence: 99%
“…20 Recent evidence also reveals that infection rates are unaffected by the use of nonsterile compared to sterile gloves during MMS and reconstruction, reinforcing the safety of outpatient dermatologic surgery. [21][22][23] Because electrosurgery is an integral component of dermatologic surgery, it is also important to consider the safety of these methods on an outpatient basis. The primary concern with respect to electrosurgery is its potential interference with implantable electrical devices, namely cardiac pacemakers and defibrillators (ICDs).…”
Section: Safety In An Office-based Setting Key Pointsmentioning
confidence: 99%